Libraries and archives in the digital age - Mizruchi, Susan L. (Palgrave Macmillan, 2020)
“This is an exciting book, one that many of us in humanities research (and book history) have been hoping to see. This collection persuasively explores the issues of digitized knowledge, access, and preservation in the widest scope, across nations as well as disciplines, libraries as well as academic departments. It offers a richly multinational and cross-cultural perspective on these issues by exploring them across borders and continents. Mizruchi’s collection brings together leading scholars in book and reading history, and digital humanities, with front-line scholars in library and information sciences to provide a unique combination of academic and curatorial expertise. I don’t know of any book that offers such a convincing combination of specialties–let alone a book that will be so readable across many categories of intellectual life. The book is beautifully conceived, interleaving through the essays its topics of print and digital, libraries and visual or other non-text archives, and overlapping professional agendas among academics, librarians, and digital specialists.” — Prof Jon Klancher, Carnegie Mellon University, USA “These authors present the case for the vitality and urgency of new forms and models of public libraries and archives, open access and the transmission of cultural and community assets, embracing the digital as essential rather than threat.” –David Leonard, President, Boston Public Library, USA The role of archives and libraries in our digital age is one of the most pressing concerns of humanists, scholars, and citizens worldwide. This collection brings together specialists from academia, public libraries, governmental agencies, and non-profit archives to pursue common questions about value across the institutional boundaries that typically separate us. Susan L. Mizruchi is the William Arrowsmith Professor in the Humanities, Director of the Humanities Center, and Professor of English at Boston University. Her books include Brando’s Smile (2014), The Rise of Multicultural America (2008), and The Science of Sacrifice (1998). She has received many academic honors, including fellowships from the Guggenheim Foundation, the Huntington Library, the Fulbright Foundation, and the National Endowment for the Humanities.
Enthält Literaturangaben
Keywords: Library science; Humanities—Digital libraries; Popular Science in Cultural and Media Studies; Library Science; Digital Humanities; History of the Book; Historiography and Method; Higher Education